Reactivity of internal vs. external Bronsted acid sites in nanosponge MFI: H/D exchange kinetic study - Bulánek, Roman; Vaculík, Jan; Vesely, Ondrej; Prech, Jan; Kubu, Martin; Rubes, Miroslav; Bludsky, Ota (Elsevier Science BV, 2022)
The strength of Bronsted acid sites (BAS) affects the properties of 2D and hierarchical zeolites, but the relative contribution of internal and external BAS remains unknown. Accordingly, this study aims to assess the acidity of external and internal BAS in nanosponge-like MFI zeolites by comparatively analyzing hydrogen-deuterium exchange kinetics between zeolitic deuteroxyl groups and C2H6 molecules monitored by in-situ FTIR spectroscopy. For this purpose, (i) a sample pre-treatment procedure was specifically developed to deuterate only internal or only external acid sites using 2,6-di-tert-butylpyridine (DTBP) as a masking agent and (ii) DFT modeling of surface BAS was performed. Theoretical models of the thin MFI layer revealed that the external surface of MFI crystals contains three types of BAS: (i) BAS positioned in 5-membered rings, either shielded by silanol nests, rendering the site inaccessible for DTBP or yielding a very low adsorption energy for ethane, (ii) BAS pointing into the pores, due to the presence of aluminol, which hinders DTBP accessibility, or the BAS undergoes transformation to a three-coordinate aluminium site, and (iii) BAS accessible to both DTBP and ethane. The results from our kinetics measurements showed that H/D exchange at external BAS of nanosponge MFI zeolites is faster than at internal BAS (rate constants at 425 degrees C: 3.8 10(-3) vs. 2.4 10(-3) s(-1) for external and internal BAS, respectively), but this cannot be attributed to the effect of diffusion. Therefore, the differences in exchange kinetics between external and internal BAS are given by mutual interplay of subtle differences in the corresponding activation barriers (113 vs. 117 kJ/mol for external and internal BAS, respectively) and pre-exponential terms (1.09 10(6) vs. 1.45 10(6) s(-1) for external and internal BAS, respectively).
Reaktivita vnitřních a vnějších Bronstedových kyselých poloh v nanoporézních MFI: kinetická studie H/D výměny
Keywords: acidity; zeolites; MFI; isotopic exchange; two-dimensional; nanosponge; DFT; theory; external sites; kyselost; zeolity; MFI; izotopická záměna; 2D; nanopóry; DFT